Interaksi Hadis dan Budaya: Interpretasi Ali Mustafa Yaqub dalam Kitab Al-Turuq Al-Sahihah Fi Fahm Al-Sunnah Al-Nabawiyah - Khalilurrahman, As'ad; Ichwayudi, Budi; Shobri, Alwi; Akbar, Riko (Program Pascasarjana, UIN Alauddin Makassar, 2024)
The source of religious teachings is the Qur'an and hadith (sayings and actions of Prophet Muhammad). The birth of both is closely related to the culture and customs of the society at that time. The Prophet used culture as a medium to convey his message. The actions of the Prophet served as an example for humanity, especially Muslims, in the world. These behaviors and traits are referred to as the